Softening of a flat phonon mode in the kagome ScV6Sn6 - A. Korshunov; H. Hu; D. Subires; Y. Jiang; D. Călugăru; X. Feng; A. Rajapitamahuni; C. Yi; S. Roychowdhury; M. G. Vergniory; J. Strempfer; C. Shekhar; et al. (Nature Communications, 2023)
Abstract Geometrically frustrated kagome lattices are raising as novel platforms to engineer correlated topological electron flat bands that are prominent to electronic instabilities. Here, we demonstrate a phonon softening at the k z  = π plane in ScV6Sn6. The low energy longitudinal phonon collapses at ~98 K and q =  $$\frac{1}{3}\frac{1}{3}\frac{1}{2}$$ 1 3 1 3 1 2 due to the electron-phonon interaction, without the emergence of long-range charge order which sets in at a different propagation vector q CDW =  $$\frac{1}{3}\frac{1}{3}\frac{1}{3}$$ 1 3 1 3 1 3 . Theoretical calculations corroborate the experimental finding to indicate that the leading instability is located at $$\frac{1}{3}\frac{1}{3}\frac{1}{2}$$ 1 3 1 3 1 2 of a rather flat mode. We relate the phonon renormalization to the orbital-resolved susceptibility of the trigonal Sn atoms and explain the approximately flat phonon dispersion. Our data report the first example of the collapse of a kagome bosonic mode and promote the 166 compounds of kagomes as primary candidates to explore correlated flat phonon-topological flat electron physics.